A comparison of the impact of extensive and intensive reading approaches on the reading attitudes of secondary EFL learners - Park, A Young (Studies in Second Language Learning and Teaching, 2020)
Extensive reading (ER) which encourages second or foreign (L2) learners to engage in a great deal of reading, has long been recognized as an efficient approach in L2 reading pedagogy. While many attempts have been made to understand the effect of ER on the cognitive domains of L2 learners, there has been insufficient investigation into how ER influences their affective domains. Particularly, reading attitudes, one of the key elements of affective factors involved in L2 reading, have received little attention. This classroom-based intervention study investigated the impact of ER on English as a foreign language (EFL) learners’ attitudes toward English reading compared to the influence of the traditional intensive reading (IR) approach. In addition, this study explored whether the impact of the ER approach on EFL learners’ reading attitudes is different depending on L2 proficiency. The study included two intact classes of EFL secondary learners (N = 72) who received either ER or IR instructional treatments for a 12-week period. For the results, ANCOVA showed that the ER approach fostered positive reading attitudes significantly more than the IR approach. In addition, the analysis indicated that the participants’ proficiency levels did not have a significant effect upon changes in their reading attitudes. That is, regardless of proficiency level, the ER approach demonstrated a significantly positive effect on participants’ reading attitudes in comparison with the IR approach.